The resolution of quadratic inequality problems in mathematics: Discrepancies between thought and action - Surya Sari Faradiba; Alifiani; Nurul Akmal Md Nasir (IKIP Siliwangi and I-MES, 2024)
This research explores the intricate relationship between students' cognitive processes and problem-solving approaches, explicitly focusing on misconceptions in solving quadratic inequalities. This study was conducted among 179 undergraduates in a mathematics education program in Malang, East Java, Indonesia; this mixed-method concurrent explanatory sequential design research employed the DISC questionnaire and quadratic inequality assignments. The DISC questionnaire categorized respondents into Dominance, Influence, Steadiness, and Conscientiousness. Data were generated from these pre-service teacher responses to the questionnaire, task assignment, and follow-up interviews to solicit information. Purposive sampling facilitated in-depth interviews, providing nuanced insights into the interplay between personality types and mathematical misconceptions. The quantitative data analysis results show a significant association between personality type and the type of error experienced by students when completing an open-ended task about quadratic inequalities X2(12) = 26.836, p = 0.008, V = 0.224. Meanwhile, qualitative data analysis findings reveal patterns associating personality types with specific misconceptions. Dominant traits are linked to theoretical misconceptions, while Influence and Conscientiousness traits correspond to conceptual misconceptions. Additionally, Steady traits are associated with classification misconceptions. This study contributes novel perspectives to mathematics education by exploring the influence of personality on mathematical cognition. The aim is to inform tailored teaching strategies for optimized learning outcomes, addressing persistent barriers posed by misconceptions in quadratic inequalities.